Potential roles for mitochondria-to-HSF1 signaling in health and disease - Labbadia, Johnathan (Frontiers in Molecular Biosciences, 2023)
The ability to respond rapidly and efficiently to protein misfolding is crucial for development, reproduction and long-term health. Cells respond to imbalances in cytosolic/nuclear protein homeostasis through the Heat Shock Response, a tightly regulated transcriptional program that enhances protein homeostasis capacity by increasing levels of protein quality control factors. The Heat Shock Response is driven by Heat Shock Factor 1, which is rapidly activated by the appearance of misfolded proteins and drives the expression of genes encoding molecular chaperones and protein degradation factors, thereby restoring proteome integrity. HSF1 is critical for organismal health, and this has largely been attributed to the preservation of cytosolic and nuclear protein homeostasis. However, evidence is now emerging that HSF1 is also a key mediator of mitochondrial function, raising the possibility that many of the health benefits conferred by HSF1 may be due to the maintenance of mitochondrial homeostasis. In this review, I will discuss our current understanding of the interplay between HSF1 and mitochondria and consider how mitochondria-to-HSF1 signaling may influence health and disease susceptibility.